1990
DOI: 10.1144/gsl.sp.1992.049.01.41
|View full text |Cite
|
Sign up to set email alerts
|

The Batain Melange of NE Oman

Abstract: Most of the Batain coast area, previously unmapped or mapped as Hawasina, is shown to be underlain by melange. This consists of blocks, up to 10 km long, of a variety of rocks in a scanty, seldom exposed sheared shaly matrix. Clasts include Triassic and younger Hawasina-type red cherts and shales; Mesozoic calciturbidites; Permian limestones and megabreccias (associated with basalts); ammonitico rosso type blocks (Triassic?); a limestone and pillow lava assemblage, probably Jurassic; Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…The 'Qarari Limestone' (sensu Shackleton et al 1990), known only from the Batain area, was assigned by Béchennec et al (1992) and Wyns et al (1992) to the Al Jil Formation. Immenhauser et al (1998) separate the Qarari Formation from the Al Jil Formation within the newly introduced Batain Group (Fig.…”
Section: A Qarari Unitmentioning
confidence: 99%
See 2 more Smart Citations
“…The 'Qarari Limestone' (sensu Shackleton et al 1990), known only from the Batain area, was assigned by Béchennec et al (1992) and Wyns et al (1992) to the Al Jil Formation. Immenhauser et al (1998) separate the Qarari Formation from the Al Jil Formation within the newly introduced Batain Group (Fig.…”
Section: A Qarari Unitmentioning
confidence: 99%
“…An Early to early Middle Permian age for the Qarari Unit was determined by Shackleton et al (1990) and Lee (1990), who mentioned an extensive fauna of fusulinids, productid brachiopods, bryozoans, corals, blastoids, crinoids and trilobites from the Jabal Qarari area. The early Late Permian age determined by Wyns et al (1992) is demonstrated by conodont assemblages with Gondolella cf.…”
Section: A Qarari Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…The northeastern margin of Oman between Ra's al Hadd and Ra's Jibsch is characterized by a complex stratigraphic setting recording major tectonic events, such as the opening of the Tethys Ocean and the obduction of the Masirah Ophiolites and associated mélange sequence [2,3]. The Batain Mélange formed due to the closure of the Batain basin and the obduction of the Masirah ophiolite along the northeastern margin of the Arabian Plate during late Maastrichtian-early Paleocene time.…”
Section: Depositional System and Discussionmentioning
confidence: 99%
“…he Batain coast in northeastern Oman in Ash-Sharyqiah region ( Figure 1) is comprised of diverse stratigraphy due to complex deformation related to the Late Cretaceous-Paleogene deformation of the Arabian Plate and closure of the Tethyan Ocean [1,2,3]. The area is part of a tectonic mélange known as the Batain Mélange [1], comprising Permian to Late Cretaceous rocks later described as the Batain Group of the Batain nappe [4].…”
Section: Introductionmentioning
confidence: 99%